Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

The question is this.

In $h(x) = \dfrac{\sqrt{x+9}-3}{x}$, show that $\displaystyle \lim_{x \to 0} \ h(x) = \frac{1}{6}$, but that $h(0)$ is undefinied.

In my opinion if I use this expression $\displaystyle \lim_{x \to 0} \dfrac{\sqrt{x+9}-3}{x}$ above with the $-3$ inside the square root I got an undefinied expression, but if I put the $-3$ out of the square and I use this expression to calculate the limit $\displaystyle \lim_{x \to 0} \dfrac{\sqrt{x+9}-3}{x}$ I will get $\frac{1}{6}$.

Hereenter image description here a print screen of the original question.

If needed i can post the Pdf of the homework.

share|improve this question
2  
Multiply on top and bottom by $\sqrt{x+9}+3$ and re-evaluate. –  mtiano Mar 28 '13 at 23:54
    
In this case when I said put the -3 out, I just wanna to say that I´m redefining the function above. –  Vinicius L. Beserra Mar 28 '13 at 23:57
1  
The question was edited from the OP's original one. I have edited it back. @ViniciusL.Beserra please make sure this represents your intent. –  anorton Mar 28 '13 at 23:58
    
The second function is a completely different function from the first function. Recheck the problem statement to ensure you have stated the initial problem correctly, and didn't misunderstand. Perhaps there is a typo, because, yes, the limit of the stated problem is undefined. that's not the case with the alteration. –  amWhy Mar 29 '13 at 0:00
    
1-you can not take $-3$ outside the squareroot as you wish $2$- The limit of the original expression is defintely not $1/6$. –  Seyhmus Güngören Mar 29 '13 at 0:04

4 Answers 4

As I stated in the comments above, and as demonstrated by anorton:

$$h(x) = \frac{\sqrt{x + 9} - 3}{x} \neq \frac{\sqrt{x+ 9 - 3}}{x} = \frac{\sqrt{x+6}}{x}$$

So ... Assuming the problem statement (from the original source) actually reads:

In $h(x) = \dfrac{\sqrt{x+9}-3}{x}$, show that $\displaystyle \lim_{x \to 0} \ h(x) = \frac{1}{6}$, but that $h(0)$ is undefined.

  • We can take the $\lim_{x\to 0} h(x)\;$ by applying L'Hopital's Rule because, as is, the limit evaluates to the indeterminate form $\frac 00$.
  • If you're not familiar with L'Hopital, then you can multiply the numerator and denominator by the conjugate of the numerator: the conjugate of $\sqrt{x + 9} - 3$ is simply $\sqrt{x + 9} + 3.\;$ Then simplify and evaluate the limit of the resulting expression. (See $(1)$ below.)

Either route taken will give you an expression for which the limit can be evaluated. And as you note: $$\lim_{x\to 0} h(x) = \dfrac 16$$

Now, why is $h(0)$ undefined? Because division by zero is undefined. Period.

But to say that the function is undefined when evaluated at $0$, i.e., that $h(0)$ is undefined is not to say that $\lim_{x \to 0} h(x)$ is undefined. Limits often exist at points for which a function is not defined. After all, the limit as $x \to a$ of $f(x)$ gives you the value to which $f(x)$ approaches as $x \to a$ , irregardless of whether the function is undefined AT $x = a$.


$(1)$ $$ \lim_{x \to 0} \frac{\sqrt{x + 9}-3}{x} = \lim_{x\to 0}\frac{\sqrt{x + 9} - 3}{x}\cdot \frac{\sqrt{x + 9} + 3}{\sqrt{x + 9} + 3}$$ $$= \lim_{x\to 0} \frac{x + 9 - 9}{x(\sqrt{x + 9} + 3)} = \lim_{x\to 0} \frac{x}{x\left(\sqrt{x + 9} + 3\right)} $$ $$ = \lim_{x\to 0}\frac{1}{\sqrt{ x + 9} + 3}= \frac{1}{6}$$


ADDED: There is clearly a typo in the original pdf of the question (the image of which you have now posted.) That is $$\lim_{x\to 0} \frac{\sqrt{x+9 - 3}}{x} = \lim_{x\to 0}\frac{\sqrt{x + 6}}{x} \to \frac{\sqrt{6}}{0}, \text{ so that} \lim_{x\to 0} h(x)\to\infty.$$

So I suspect that was intended for this problem (without the misprint) is the function highlighted above, whose limit, as you observe, is then $1/6$. In either case, though, $h(0)$ is undefined, because we cannot divide by zero.

share|improve this answer

To show something slightly different than the other answers: $$\begin{align} \lim_{x \to 0} \frac{\sqrt{x + 9}-3}{x} &= \lim_{x\to 0}\frac{\sqrt{x + 9}-3}{x}\frac{\sqrt{x + 9}+3}{\sqrt{x + 9}+3} \\&= \lim_{x\to 0} \frac{x+9-9}{x(\sqrt{x + 9}+3)} \\&= \lim_{x\to 0}\frac{1}{\sqrt{x+9}+3} \\ &= \frac{1}{6}. \end{align} $$ Clearly the function isn't defined at $0$ because then you are dividing by $0$.

share|improve this answer
    
There is an $x$ missing after the $3$ in the second row. But this way might be easier if one is not familiar with the rule of L'Hospital. –  cthl Mar 29 '13 at 0:46
    
I think the braces in the second row were not there when I said the $x$ was missing. Now it's okay. –  cthl Mar 29 '13 at 11:42
    
Why is the first expression discontinuous at $x=0$, but the last expression is continuous at $x=0$ (despite the fact that they're algebraically equivalent? –  alexqwx Sep 20 at 20:23

You cannot pull the negative 3 out of the square root. For example: $$\sqrt{1-3} = \sqrt{2}i \ne \sqrt{1} - 3 = -2$$

share|improve this answer

Of course $h(0)$ is undefined as you cannot divide by zero. As you said $\displaystyle\lim_{x\rightarrow 0}\frac{\sqrt{x+9}-3}x=\frac 1 6$, according to L'Hospital's rule. Why do you care about $\displaystyle\frac{\sqrt{x+9-3}}x\ne h(x)$?

share|improve this answer
1  
Yes. Clearly the original problem from the text had the $-3$ not under the radical sign. The OP mistook that "placing it in or out" as the "reason" $h(0)$ is undefined (missing the point of zero division). +1 –  coffeemath Mar 29 '13 at 0:14

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.